Thrombolysis for Suspected Intrapump Thrombosis in Patients With Continuous Flow Centrifugal Left Ventricular Assist Device. Issue 3 (4th February 2013) - Muthiah, Kavitha; Robson, Desiree; Macdonald, Peter S.; Keogh, Anne M.; Kotlyar, Eugene; Granger, Emily; Dhital, Kumud; Spratt, Phillip; Jansz, Paul; Hayward, Christopher S.
Abstract The current recommended anticoagulation regimen during continuous flow centrifugal left ventricular device support is a combination of antiplatelet therapy as well as oral anticoagulation. Despite this, pump thrombosis occurs in rare situations. We report the risk factors and nonsurgical management and outcomes of five patients implanted with continuous flow centrifugal left ventricular assist devices who displayed clinical, hemodynamic, and laboratory features of intrapump thrombosis. This information may support the use of intravenous thrombolytics for suspected pump thrombus in these newer generation devices.